Dietary Pattern and Nutritional Intake: Implications for the Nutritional Status of Papuan University Students in Surabaya - Adriana Krispul; Trias Mahmudiono (Media Gizi Kesmas, 2025)
Background: The double burden of malnutrition, including rising obesity rates, has become a global health challenge, including in Indonesia. In 2024, 23.4% of Indonesian adults were classified as obese, exceeding the national target of 21.8%. Papuan students pursuing higher education in Surabaya City face a similar situation, which is closely linked to unbalanced dietary habits and inadequate nutritional intake. Objectives: This study aims to analyze the relationship between balanced nutrition, nutrient intake, and nutritional status among Papuan college students in Surabaya City. Methods: This quantitative observational study employed a cross-sectional design. A total of 97 Papuan students enrolled in universities in Surabaya City were selected using probability sampling. Data collected included respondent characteristics, height, weight, dietary patterns, and nutrient intake. Dietary patterns were assessed using a 5-point scoring system based on Isi Piringku compliance. Data were gathered through questionnaires and 24-hour dietary recalls. Chi-square and Spearman’s rho tests were used for statistical analysis. Results: The findings showed that most respondents were 19 years old (24.7%), female (56.7%), and had a monthly allowance greater than IDR 1,000,000 (66%). More than half of the respondents had imbalanced dietary patterns, excessive nutrient intake, and were categorized as obese. There were significant relationships between dietary patterns (p=0.001; r=0.017), nutrient intake (p=0.001; r=0.869), and nutritional status among Papuan university students. Conclusion: This study concludes that balanced dietary patterns and adequate nutrient intake are associated with nutritional status. The more inappropriate the dietary intake, the higher the risk of abnormal nutritional status. Efforts to increase nutrition knowledge among Papuan students are necessary to promote healthy and balanced eating behaviors.